Switchable zinc(II)-responsive globular β-sheet peptide [research data] - Pham, Truc Lam; Kovermann, Michael; Thomas, Franziska (Universität, 2022)
The natural function of many proteins depends on their ability to switch their conformation driven by environmental changes. In this work, we prese...
Gesehen am 19.01.2022
Keywords: Forschungsdaten; Datenbank